SnSe nanoplates swallowed in carbon nanofibers as the self-standing anode for lithium-ion and sodium batteries with enhanced performance. (8th February 2023) - Yin, Hong; Li, Huaiyu; Zhao, Han; Gan, Zongsong; Hou, Zhaohui; Li, Chong; Zhu, Ming-Qiang
Abstract: SnSe is a promising anode candidate for both lithium-ion and sodium batteries (LIBs and SIBs) with high theoretic capacities, low toxicity and abundant resources. However, it suffers a short cycling life due to the poor conductivity and volume expansion when used as anode material. To improve its Li/Na storage properties, SnSe nanoplates are encapsulated in carbon nanofibers formation a 3D conductive network via a moderate electrostatic spinning and heat treatment. The modified SnSe anode exhibits textile-like feature with extensively mechanical flexibility, and was directly used as anode without and additives for both LIBs and SIBs. It delivers an excellent cycle performance with a high capacity (598 mA h g −1 after 400 cycles for LIBs and 240 mA h g −1 after 250 cycles for SIBs), which are modify enhanced comparing with reported works. The effective strategy can provide an available approach to build self-standing and flexible architecture, which is beneficial for the design of electrode materials for SIBs. Highlights: The SnSe@CNF is used as binder-free anode for LIBs and SIBs. The SnSe@CNF anode can deliver a long cycling life for flexible LIBs and SIBs. The superior performance is the high conductivity and restraining volume.